A Conceptual Model for Promoting Self-Directed Learning in Online Learning Environment - Yeyisani Evans Makhubele (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
It is important in educational research to identify the key factors affecting self-directed learning when using Moodle as an online Learning Management system. The aim of this study is therefore to develop a research-based conceptual framework for understanding SDL in Moodle online learning contexts. To establish a robust foundation for the conceptual model, a comprehensive literature review was conducted. This review employed a multi-pronged approach, using broad keyword searches across academic databases like ERIC, JSTOR, and Google Scholar. The criteria used for selecting literature included relevance, credibility, and currency. This conceptual framework contributes significantly to both theory and practice of online learning that promotes self-directed learning. The framework may be used in developing instruments for promoting online self-directed learning. The developed conceptual framework could benefit all who are involved in supporting quality online education, in an effort to develop and impactful online practice that aligns with the corresponding educational needs, services, and resource.